2020
DOI: 10.1126/science.aav7515
|View full text |Cite
|
Sign up to set email alerts
|

Keystone predators govern the pathway and pace of climate impacts in a subarctic marine ecosystem

Abstract: Predator loss and climate change are hallmarks of the Anthropocene yet their interactive effects are largely unknown. Here, we show that massive calcareous reefs, built slowly by the alga Clathromorphum nereostratum over centuries to millennia, are now declining because of the emerging interplay between these two processes. Such reefs, the structural base of Aleutian kelp forests, are rapidly eroding because of overgrazing by herbivores. Historical reconstructions and experiments reveal that overgrazing was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 40 publications
1
56
0
1
Order By: Relevance
“…The alteration in the trophic structure of marine ecosystems supports the concerns regarding the consequences of trophic downgrading (Estes et al, 2011), which can be characterized by trophic cascades due to the decrease in predator biomass. Indeed, several studies showed the impacts of top predator depletion on marine ecosystem functioning (Baum & Worm, 2009; Estes et al, 2016; Ferretti et al, 2010; Heithaus et al, 2008) and stability (Britten et al, 2014; Rasher et al, 2020). Despite their low biomass (compared to the lower TLs), predators at TL higher than 3.5 currently support more than 35% of the world fisheries (Branch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in the trophic structure of marine ecosystems supports the concerns regarding the consequences of trophic downgrading (Estes et al, 2011), which can be characterized by trophic cascades due to the decrease in predator biomass. Indeed, several studies showed the impacts of top predator depletion on marine ecosystem functioning (Baum & Worm, 2009; Estes et al, 2016; Ferretti et al, 2010; Heithaus et al, 2008) and stability (Britten et al, 2014; Rasher et al, 2020). Despite their low biomass (compared to the lower TLs), predators at TL higher than 3.5 currently support more than 35% of the world fisheries (Branch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since the direct effects of contaminants frequently reduce species diversity, indirect effects on ecosystem processes and services occur as species are reduced in abundance or extirpated. Much of the discussion of community theory and indirect effects centers on keystone species [50] and the loss of a sensitive keystone species may have significant long-term indirect consequences on ecosystem function [51]. The loss of biodiversity may also diminish the ability of communities to persist and be resilient after disturbances including from pollution events [52], or it may increase the possibility that the community will enter an alternative state that changes the ecosystem function for an extended period of time.…”
Section: Indirect Effects and Community Ecologymentioning
confidence: 99%
“…Indirect contaminant effects are being shown to affect many environmental issues and to foster unexpected or potentially undesirable outcomes. Indirect effects on ecosystem function have been found to affect biodiversity [4], be caused by invasive species [67,68], to occur during conservation efforts [69] and during habitat restoration [70,71], and after large-scale disturbance events such as oil spills [72,73], eutrophication [74], and climate change [51,75]. One concerning possibility is that pre-existing levels of contamination may affect the rate of recovery of biological functions after habitat restoration (e.g., wetland construction in areas in which soil contamination was not mitigated prior to construction); if the restored habitat is attractive to colonists, a so-called ecological trap may occur in which an existing contaminant load may reduce the survivorship or reproductive potential of colonists, slowing increases in biodiversity and the recovery of ecological function [76].…”
Section: Ecosystem Function/services and Indirect Effectsmentioning
confidence: 99%
“…Such phenomena can reduce some of the most productive ecosystems on the planet (Schiel and Foster 2015) to low productivity "urchin barrens" (Filbee-Dexter and Scheibling 2014). Although urchins inhabiting these food-depauperate barrens face starvation, many survive in these barrens for years or decades by eating food subsidies from drift algae (Rodrı ´guez 2003, Vanderklift and Wernberg 2008, Britton-Simmons et al 2009, Renaud et al 2015, Quintanilla-Ahumada et al 2018, pelagic salps (Duggins 1981), tubeworms (N. B. Spindel and D. K. Okamoto, personal observation), as well as encrusting and filamentous algae, microbial mats, and slow-growing species resistant to herbivory (Ling and Johnson 2009, Filbee-Dexter and Scheibling 2014, Rasher et al 2020. Despite food subsidies from both endogenous production and exogenous inputs, many urchins in barrens likely experience prolonged food deprivation.…”
mentioning
confidence: 99%